2021
DOI: 10.33394/hjkk.v9i2.4500
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Modul Pembelajaran Kontekstual Terintegrasi Augmented Reality untuk Meningkatkan Keterampilan Berpikir Kritis Siswa

Abstract: Pandemi Covid-19 membuat sistem pembelajaran di kelas menjadi terbatas sehingga siswa dituntut untuk belajar lebih mandiri. Akan tetapi, sumber belajar memadai yang mendukung kemandirian belajar kimia di SMAN 1 Batulayar masih sangat kurang. Penelitian ini bertujuan untuk mengembangkan modul pembelajaran kontekstual terintegrasi Augmented Reality untuk meningkatkan keterampilan berpikir kritis siswa pada materi ikatan kimia. Penelitian ini termasuk metode Penelitian dan Pengembangan. Tahapan penelitian mengiku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Based on student responses in Table 9 and Table 10, the use of contextual chemistry textbooks helps students overcome difficulties in understanding hydrocarbon material. This finding also received support from research by Mashami et al, (2021) which showed that contextual learning modules integrated with augmented reality succeeded in improving students' critical thinking skills on chemical bonding material. In addition, research by Giri et al, (2020) shows that the contextual approach is very effective in learning electrochemistry, with the experimental group achieving a higher level of mastery of learning outcomes than the control group.…”
Section: Usnul Hotimahmentioning
confidence: 57%
See 1 more Smart Citation
“…Based on student responses in Table 9 and Table 10, the use of contextual chemistry textbooks helps students overcome difficulties in understanding hydrocarbon material. This finding also received support from research by Mashami et al, (2021) which showed that contextual learning modules integrated with augmented reality succeeded in improving students' critical thinking skills on chemical bonding material. In addition, research by Giri et al, (2020) shows that the contextual approach is very effective in learning electrochemistry, with the experimental group achieving a higher level of mastery of learning outcomes than the control group.…”
Section: Usnul Hotimahmentioning
confidence: 57%
“…In this regard, researchers hope to be able to produce products in the form of quality textbooks in accordance with quality criteria and standards that can help students understand and master chemistry lessons and increase students' understanding of concepts. In related research, Mashami et al, (2021) found that contextual learning modules integrated with augmented reality were effective in improving students' critical thinking skills. Wulandari et al, (2019) show that the development of contextual-based modules on colloidal materials meets the National Education Standards Agency (BSNP).…”
Section: Introductionmentioning
confidence: 99%
“…These contextual problems can be related to theoretical knowledge in class with everyday life situations. Other supporting research is (Mashami et al, 2021) explained that contextual learning modules containing material explanations based on problems or facts around humans can build students' thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the development of AR-assisted modules as learning media [36], [37], [38]. For example, AR-assisted modules are used to increase learning motivation [39], concept understanding [40]; critical thinking skills [41]. However, although many AR-assisted modules have been developed, the problem of student learning independence has not been completed, especially in the Cultural Anthropology course.…”
Section: Recheck Subject Predicate Object Description and Letter Errorsmentioning
confidence: 99%